Enantioselective total synthesis of (−)-colchicine, (+)-demecolcinone and metacolchicine: determination of the absolute configurations of the latter two alkaloids. Issue 7 (15th May 2017) - Chen, Bo; Liu, Xin; Hu, Ya-Jian; Zhang, Dong-Mei; Deng, Lijuan; Lu, Jieyu; Min, Long; Ye, Wen-Cai; Li, Chuang-Chuang
Abstract : A highly concise, enantioselective synthesis of (−)-colchicine, the first syntheses of (+)-demecolcinone and metacolchicine, was reported. Abstract : Here, we describe a concise, enantioselective, and scalable synthesis of (−)-colchicine (9.2% overall yield, >99% ee). Moreover, we have also achieved the first syntheses of (+)-demecolcinone and metacolchicine, and determined their absolute configurations. The challenging tricyclic 6-7-7 core of colchicinoids was efficiently introduced using an intramolecular oxidopyrylium-mediated [5 + 2] cycloaddition reaction. Notably, the synthesized colchicinoid23 exhibited potent inhibitory activity toward the cell growth of human cancer cell lines (IC50 = ∼3.0 nM), and greater inhibitory activity towards microtubule assembly than colchicine, making it a promising lead in the search for novel anticancer agents.